First Occurrence of Tetrazines in Aqueous Solution: Electrochemistry and Fluorescence. Issue 17 (4th November 2015) - Fritea, Luminiţa; Audebert, Pierre; Galmiche, Laurent; Gorgy, Karine; Le Goff, Alan; Villalonga, Reynaldo; Săndulescu, Robert; Cosnier, Serge
Abstract: The photophysical and electrochemical properties of tetrazines substituted by linear 2, 3‐naphtalimide antennas and/or adamantane groups specifically dedicated to host–guest interactions with cyclodextrins are studied both in organic and aqueous media. In acetonitrile solvent, the reduction potential of tetrazine leading to the anion radical is shifted, depending on the electron‐withdrawing power of the substituent of the tetrazines. Due to the hydrophobic character of these compounds, their solubilization in aqueous solution is achieved successively in presence of either β‐cyclodextrins or gold nanoparticules modified by β‐cyclodextrins. We demonstrate that the formation of the inclusion compound tetrazine–cyclodextrin allows the solubilization of the tetrazines in aqueous solution. The supramolecular assemblies obtained in water retain tetrazine's emission properties, yielding a yellow fluorescence. Abstract : Help from a host : Substituted tetrazines are solubilized for the first time in water thanks to host–guest interactions with cyclodextrins. Emission and electrochemical properties confirm the formation of these supramolecular structures.